PENGATURAN ANTI DUMPING DALAM HUKUM GATT-WTO DAN IMPLEMENTASINYA DI INDONESIA: Ghazwan Aqrabin Faqih - Ghazwan Aqrabin Faqih (Samudra Publisher, 2023)
This research aims to discuss the basis for anti-dumping regulations in WTO law and the implementation of WTO anti-dumping rules in Indonesia. This research is normative research with a statutory approach and a conceptual approach. Anti-Dumping Regulations in GATT-WTO Regulations. Internationally, the provisions for anti-dumping regulations are regulated in Article VI General Agreement on Tariffs and Trade (GATT) 1947 and as a step used to prevent dumping practices, then in 1967 it was implemented. signed the